MULTIPLIKASI PLANLET KENTANG (Solanum tuberosum L.) SECARA IN VITRO PADA MEDIA MS DENGAN PENAMBAHAN NAA DAN AIR KELAPA - Faridatul Mukminah; Miranty Trinawaty; Teguh Prihatin (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2021)
This study aims to find appropriate media formulations for plant propagation of potato in vitro. Research conducted at the Tissue Culture Laboratory of the Faculty of Agriculture, University of Tridinanti Palembang, beginning July 2015 until October 2015.The research design used is Completely Randomized Design (CRD) arranged in factorial, with 9 (nine) combined treatment and five (5) replications ie: N1A1 = 0.5 ppm NAA + 100 ml/l coconut water, N1A2 = 0.5 ppm NAA + 150 ml/l coconut water, N1A3 = 0.5 ppm NAA + 200 ml/l coconut water, N2A1 = 1 ppm NAA + 100 ml/L coconut water, N2A2 = 1 ppm NAA + 150 ml/l coconut water, N2A3 = 1 ppm NAA + 200 ml/l coconut water, N3A1 = 1.5 ppm NAA +100 ml/l coconut water, N3A2 = 1.5 ppm NAA + 150 ml/l coconut water, and N3A3 = 1.5 ppm NAA + 200 ml/l coconut water. The observation parameter are the time to established buds, shoots high, the time to established roots, number of roots, root length, and the percentage of plantlets life.The results showed that treatment of NAA at a concentration of 1 ppm affected significant on the root length 7.74 cm. Coconut water at a concentration of 100 ml/l significantly affected the established of root ie 9.97 days after planting (dap) and 200 ml/l of coconut water has a significant effect on shoot height 10.27 cm. There was no significant interaction between NAA and coconut water in almost of all parameters were observed, except on the parameter of established roots. NAA at a concentration of 1.5 ppm and 200 ml/l of coconut water has a significant interaction for paremeter time to established roots ie 7.00 dap.